Maine’s Investment Imperative - Lachance, Laurie (Maine Policy Review, 2002)
In the past two decades, Maine’s per capita income ranking has not topped 27th, and in recent years, the state’s relative position has dropped to 36th. More importantly, the gap between Maine and the United States has increased since 1990. In this article, Maine’s State Economist Laurie Lachance lays out a long-term investment strategy for Maine that focuses on education, research and development, comprehensive tax reform, greater efficiencies in the delivery of state and local services, and limits on government spending. Lachance argues that choices must be made even in times of fiscal crisis. Failure to invest means failure, period.
Keywords: Maine economy; Maine demographics